rancang bangun sistem informasi pemesanan iklan berbasis web pada cv.visi mitra media - Prasetya, Rengga Adi; Retnawati, Lestari (Melek IT : Information Technology Journal, 2023)
The installation of billboards, towers and billboards is the most efficient way of marketing a product because the installation location is easily accessible and found by the community of potential consumers so that goods or service companies compete to market products through advertising along the road. But not a few customers who face obstacles in the ordering process who still use the manual method in providing sales information. CV Vision Media partners have a vision and mission by expanding trade throughout Indonesia but the mission has not been realized, therefore, the purpose of writing a final project proposal This is to help realize a CV Visi Mitra Media mission to expand the range of orders throughout Indonesia by creating a dynamic web-based. The results and discussion of the results of the system that has been made and tested using black box testing, the results are all validated, conclusions and suggestions we can see in the discussion at the beginning. E-Commerce. The system is made web-based with PHP programming language, and MySQL database. The software development methodology used in the system is the waterfall method.